Accurate Prediction of Melt Electrowritten Laydown Patterns from Simple Geometrical Considerations. Issue 12 (29th October 2020) - Hrynevich, Andrei; Liashenko, Ievgenii; Dalton, Paul D.
Abstract: Melt electrowriting (MEW), an electrohydrodynamic additive manufacturing technology, can produce polymer structures with micrometer resolution. Unlike conventional direct writing of fluids, the laydown pattern often deviates from the programmed one, due to a lag in the electrified jet. MEW of increasingly complex patterns currently entails a cumbersome trial‐and‐error procedure of adjusting printing parameters to ensure good accuracy. This issue is addressed with a geometrical model that predicts the expected printed fiber path, based on the coded trajectory, critical translation speed, and the collector speed. The influence of the process parameters on the jet lag is investigated and a general equation for the lag computation is implemented into the model. The presented model can evaluate the printing result up to ten times more accurate than the designed collector movement path and thus assist in identifying printing defects and adjustment of the printing G‐code in advance. Abstract : A geometrical model is developed as a simple tool for the prediction of a melt electrowritten fiber laydown pattern onto a flat surface. The proposed geometrical model assists in scaffold design and manufacturing by providing the first layer print results, and thus aids in the adjustment of settings to obtain the intended direct‐written shape.